Lexical vs. compositional Agency: The role of the context in licencing Agency - Ježek, Elisabetta (Verbum – Analecta Neolatina, 2025)
In this paper, we propose a taxonomy of verbs based on their compositional behaviour regarding Agency. The taxonomy comprises three primary classes: agent-selecting verbs, non-agent-selecting verbs, and verbs that are lexically underspecified regarding Agency. We describe the semantic and syntactic characteristics of each class using evidence from corpora and considering the potential influence of coercive phenomena in semantic composition, which may be prompted by contextual cues such as agent-oriented or patient-oriented adverbials (intentionally, accidentally). Our analysis focuses on Italian, but the conclusions generally apply to other languages as well.